\(\frac{22}{9}-\left(x+\frac{1}{2}\right)^2=\frac{7}{3}\)
\(\left(x+\frac{1}{2}\right)^2=\frac{22}{9}-\frac{7}{3}\)
\(\left(x+\frac{1}{2}\right)^2=\frac{1}{9}\)
\(\left(x+\frac{1}{2}\right)^2=\left(\frac{1}{3}\right)^2\)
\(\Rightarrow x+\frac{1}{2}=\frac{1}{3}\)
\(x=\frac{1}{3}-\frac{1}{2}\)
\(x=-\frac{1}{6}\)
\(\frac{22}{9}-\left(x+\frac{1}{2}\right)^2=\frac{7}{3}\)
\(\left(x+\frac{1}{2}\right)^2=\frac{22}{9}=\frac{7}{3}\)\
\(\left(x+\frac{1}{2}\right)^2=\frac{22}{9}-\frac{21}{9}\)
\(\left(x+\frac{1}{2}\right)^2=\frac{1}{9}\)
\(\Rightarrow x+\frac{1}{2}=\pm\frac{1}{3}\)
TH1:\(x+\frac{1}{2}=\frac{1}{3}\)
\(x=\frac{1}{3}-\frac{1}{2}\)
\(x=-\frac{1}{6}\)
TH2:\(x+\frac{1}{2}=-\frac{1}{3}\)
\(x=-\frac{1}{3}-\frac{1}{2}\)
\(x=-\frac{5}{6}\)
Vậy \(x\in\left\{-\frac{1}{6};-\frac{5}{6}\right\}\)
x +(22/9 -1/2) =7/3
x +(44/18-9/18)=7/3 + 35/18
x =42/18+35/18
x =77/18
k nha bạn